EFFECT OF IRON SUPPLEMENTED DIET ON THE GROWTH OF THE INDIAN MAJOR CARP, CIRRHINUS MRIGALA - SHIBU, S.; JOSY, SINDHU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The fry of Cirrhinus mrigala were fed with fish meal based prepared diet supplemented with graded levels of ferric chloride 0,200,400 and 600 mg/kg of diet for a period of 40 days. A concentration of 200 mg ferric chloride per kg of feed is found optimum for growth enhancement in C. mrigala, while higher concentration of this mineral exhibited retarded growth as compared to control diet. The anabolic role of Fe" ' " in C. mrigala is discussed.